Proof of concept for biorefinery approach aiming at two bioenergy production compartments, hydrogen and biodiesel, coupled by an external membrane. Issue 2 (4th March 2018) - Béligon, Vanessa; Noblecourt, Alexandre; Christophe, Gwendoline; Lebert, André; Larroche, Christian; Fontanille, Pierre
ABSTRACT: A biorefinery is a facility that integrates biomass conversion processes and equipment to produce fuels, power and chemicals from biomass. This concept is applied here to hydrogen production by anaerobic fermentation. Its biological production is increasingly perceived as a potential pathway for developing renewable sources of energy, due to hydrogen's high energy content (142 kJ g −1 ) and the absence of harmful emissions during utilization in a hydrogen fuel cell. The main secondary metabolites produced during dark fermentation (volatile fatty acids, VFAs) are building blocks and can also serve as an alternate carbon source for lipid production from oleaginous yeast strains for biodiesel production. The concept proposed here is the coupling of two main compartments. In the first one, lignocellulosic biomass is transformed by dark fermentation into hydrogen and VFAs. The medium used in the first compartment is transferred via an immersed membrane bioreactor to the second compartment where the production of single-cell oil with oleaginous yeast occurs using VFAs as carbon source. This study aims at presenting the feasibility of this bioprocess, through hydrogen production from glucose followed by lipid production by the oleaginous yeast Cryptococcus curvatus grown on the VFA-enriched supernatant resulting from the dark fermentation step.